Franklinothrips; a pantropical Thysanoptera genus of ant-mimicking obligate predators (Aeolothripidae) - Mound, Laurence A.; Reynaud, Philippe (Zootaxa, 2005)
The Aeolothripidae genus Franklinothrips Back is redefined with a key provided to the 14 species recognised worldwide, of which F. brunneicornis from New Caledonia and F. strasseni from Nepal are described as new. Most of the species appear to be bisexual and localised in distribution, but F. vespiformis is usually unisexual and is found in many tropical countries, here being recorded from Australia for the first time. All of the species are probably predatory, as adults and larvae, three species having been promoted as biological control agents against pest thrips in European greenhouses. Comments are given on predation and ant-mimicry amongst Aeolothripidae.